2007
DOI: 10.1002/hep.21844
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype of hepatitis B virus–specific T cells differ in the liver and blood in chronic hepatitis B virus infection

Abstract: H epatitis B virus (HBV)-specific T cells are im-portant in the successful clearance of acute HBV infection but also mediate liver damage in both acute and chronic HBV infections. In individuals with chronic HBV infection, circulating HBV-specific T cells are detected infrequently and are significantly reduced compared with individuals who recover from acute HBV infection. [1][2][3] We recently developed a sensitive method to assess HBV-specific T cells using an overlapping peptide library and intracellular cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…Intracellular cytokine staining (ICS) was performed as previously described (7). Briefly, 200 l of fresh whole blood was incubated for 6 h at 37°C with an overlapping HBV peptide library that covered the entire HBV genome and was designed for the genotype A consensus sequence and included additional peptides for genotypes B, C, and D in areas of high variability (8,9) or with HIV-1 Gag peptides (obtained through the AIDS Research and Reference Reagent Program, Division of AIDS, National Institute of Allergy and Infectious Diseases, National Institutes of Health) and either DMSO as a negative control or pokeweed mitogen (PWM; Sigma) and staphylococcal enterotoxin B (SEB; St. Louis, MO) as positive controls (Fig. 1).…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular cytokine staining (ICS) was performed as previously described (7). Briefly, 200 l of fresh whole blood was incubated for 6 h at 37°C with an overlapping HBV peptide library that covered the entire HBV genome and was designed for the genotype A consensus sequence and included additional peptides for genotypes B, C, and D in areas of high variability (8,9) or with HIV-1 Gag peptides (obtained through the AIDS Research and Reference Reagent Program, Division of AIDS, National Institute of Allergy and Infectious Diseases, National Institutes of Health) and either DMSO as a negative control or pokeweed mitogen (PWM; Sigma) and staphylococcal enterotoxin B (SEB; St. Louis, MO) as positive controls (Fig. 1).…”
Section: Patient Populationmentioning
confidence: 99%
“…Second, we were able to measure the production of IFN-␥ and TNF-␣ only from HBV-specific T cells because we had access only to a four-color flow cytometer in Thailand. We selected these two cytokines, in preference to others such as interleukin-2 (IL-2) and IL-10, because our previous study of HBV monoinfected patients identified IFN-␥ and TNF-␣ as being produced in greater magnitude and frequency than either IL-2 or IL-10 in HBV-specific CD8 ϩ T cells in the blood and liver (8). In addition, both IFN-␥ and TNF-␣ have been demonstrated to be important in the cytolytic and noncytolytic clearance of HBV (15).…”
Section: -Cell Responses In Hiv-hbv Coinfection 2663mentioning
confidence: 99%
“…Intracellular-cytokine staining (ICS) was performed as previously described by stimulating fresh blood with an overlapping peptide library for the HBV proteome, including genotypes A, B, C, and D (16,17) and HIV-1 Gag (obtained through the AIDS Research and Reference Reagent Program, Division of AIDS, National Institute of Allergy and Infectious Diseases, National Institutes of Health), to define cytokine-producing HBVspecific and HIV-1 Gag-specific CD8 ϩ T cells. Dimethyl sulfoxide with costimulatory molecules (CD28 and CD49d monoclonal antibodies) was used as a negative control, and pokeweed mitogen (Sigma) and staphylococcal enterotoxin B (Sigma) were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…ϩ T cells above background and, in addition, at least twofold above background (10,16,21). To determine the specificity of the response, we calculated the mean response to each gene product as a proportion of the total proteome response for all patients.…”
Section: Cd8mentioning
confidence: 99%
“…T-cell response in HBV infection mainly initiates Th2 immune response rather than Th1. The production of IL-10 was reported in many researches but the Th1 responses and cytokine production are weak when compared with resolver [43,44].…”
Section: Monocytes/macrophages In Hbv Infectionmentioning
confidence: 99%